LESSON STUDY: A MODEL OF RECONSTRUCTION OF TEACHER’S PEDAGOGICAL EXPERIENCE - Sudirman Sinring (FKIP ULM, 2021)
The teacher's pedagogical experience is the basis for improving the quality of learning. This study aims to reconstruct the pedagogical experience for elementary school teachers through the Lesson Study (LS) Model. A quasi-qualitative approach explored this study. A total of 20 teachers, a principal and a school supervisor were directly involved. The activities were identification of problems, brainstorming, designing, modelling, reflection, re-designing and re-modelling. The data was collected by class observation, questionnaire, and interview. Data is analyzed by percentage and qualitatively. The results found, as many as 80,63% of participants stated that LS agreed, and 19,37% positively agreed to reconstruct the teacher's pedagogical experiences. Thus, the LS model was very effective in reconstructing more qualified pedagogical experience of elementary school teachers in Bone Regency. The main advantage of LS was desired change by directly events. Keywords: Collaborative; Experience; Lesson Study; Pedagogy; Reconstruct